Electrochemical Conversion of Cu Nanowire Arrays into Metal-Organic Frameworks HKUST-1. Issue 2 (1st February 2023) - Luo, Jia; Lan, Mu; Wagner, Michael; Ulrich, Nils; Kopold, Peter; Tzifas, Ioannis; Wang, Hongyan; Trautmann, Christina; Toimil-Molares, Maria Eugenia
Abstract : We explore the conversion of free-standing Cu nanowire arrays produced by electrodeposition in polymer etched ion-track membranes into metal-organic frameworks KHUST-1 by electrochemical oxidation. HKUST-1 particles are built up when the as-formed Cu 2+ ions bind to the benzene tricarboxylic acid ligands (BTC 3− ) in the electrolyte solution. The morphology and crystallinity of the samples at different transformation stages are investigated by scanning and transmission electron microscopy. X-ray diffraction data taken at different conversion times confirm the formation of HKUST-1 particles. The conversion process resulted in octahedral structures of several μ m in size. Comparison of the Raman spectra with the band positions derived from density functional theory (DFT) calculations, suggests that vibrations involving Cu atoms appear only below 490 cm −1 wavenumbers and involve the entire HKUST-1 lattice rather than vibrations of single bonds.